Efficacy of different acupuncture-related therapies for tension-type headache: a systematic review and network meta-analysis - Yimeng Wang; Wang Lu; Yongjun Wang; Wei Chen; Haiyin Zhao (Frontiers in Neurology)
BackgroundTension-type headache (TTH) is among the most common primary headache disorders, characterized by recurrent episodes that are difficult to manage, thus posing a significant public health challenge. Acupuncture, a well-recognized non-pharmacological treatment, is frequently employed for pain management, including TTH. However, the variety of acupuncture techniques and inconsistent treatment outcomes underscore the need for a thorough evaluation. This study aims to update the current evidence on acupuncture and related therapies for TTH, evaluate the efficacy and safety of various acupuncture therapies, and identify the most effective therapeutic strategies, providing valuable guidance for clinical practice.MethodsWe systematically searched randomized controlled trials (RCTs) from four English databases (PubMed, Embase, Cochrane Library, and Web of Science) and four Chinese databases (Wanfang, VIP, CNKI, and SinoMed), including gray literature, up to April 19, 2024. The outcome measures included headache frequency, duration, pain intensity, and responder rate. A Bayesian network meta-analysis was conducted using Stata 17.0 to assess the relative effectiveness and safety of the different acupuncture therapies. This study was registered with the Prospective Register of Systematic Reviews (CRD42024537187).ResultsA total of 42 RCTs, encompassing 4,103 participants and 21 distinct treatment therapies, were included in the analysis. The network meta-analysis yielded the following findings: (1) regarding responder rate, several acupuncture or combined acupuncture and medication approaches, such as electro-acupuncture (EA) + cupping therapy (CT) [odds ratio (OR) = 28.66, 95% CI: 1.68 to 487.35], manual acupuncture (MA) + bloodletting therapy (BT) (OR = 6.07, 95% CI: 1.81 to 20.29), plum blossom needle tapping (PBNT) (OR = 3.76, 95% CI: 1.04 to 13.65), and scalp acupuncture (SPA) (OR = 3.65, 95% CI: 2.29 to 5.83), were significantly more effective than western medicine (WM) alone, with EA + CT (92.1%) being the most effective. (2) In terms of reducing headache frequency, EA (85.9%) was the most effective, followed by MA + PBNT (80.9%) and MA + WM (78.4%). Compared to WM, both MA + PBNT (SMD = −1.76, 95% CI: −3.31 to −0.22) and EA (SMD = −1.75, 95% CI: −3.30 to −0.20) significantly reduced headache frequency. (3) For shortening headache duration, EA (83.9%) emerged as the most effective treatment, followed by MA + WM (73.5%) and laser acupuncture (LA) (68.5%). (4) In terms of pain intensity reduction, the MA + WM combination (89.4%) was superior to other treatments, with SPA + WM (77.7%) being the next most effective. Compared to herbal medicine (HM), both MA + WM (SMD = −2.37, 95% CI: −4.20 to −0.55) and MA alone (SMD = −1.00, 95% CI: −1.75 to −0.24) significantly alleviated pain intensity.ConclusionThis comprehensive analysis of 21 acupuncture and related therapies demonstrates that EA is the most effective in reducing headache frequency and shortening headache duration, while EA + CT and MA + WM are the optimal therapies for enhancing responder rate and reducing pain intensity, respectively. However, clinical decisions should be individualized based on the specific needs of each patient.Systematic review registrationThe study protocol was registered on the PROSPERO database under registration number CRD42024537187 (https://www.crd.york.ac.uk/prospero/#recordDetails).